Cost-effectiveness analysis of ultra-hypofractionated radiotherapy and conventionally fractionated radiotherapy for intermediate- to high-risk localized prostate cancer - He, Jiaoxue; Wang, Qingfeng; Hu, Qiancheng; Li, Changlin (Frontiers in Oncology, 2023)
Background: Radiotherapy is an effective curative treatment option for intermediate-to-high-risk localized prostate cancer. According to HYPO-RT-PC trial (ISRCTN45905321) ，there was no significant difference in 5 years of follow-up failure-free survival,overall survival,urinary toxicity,bowel toxicity, erectile function decreased between ultra-hypofractionated radiotherapy with conventionally fractionated radiotherapy, except that the incidence of urinary toxicity in ultra-hypofractionated radiotherapy was higher at 1 years follow-up. We evaluated the cost-effectiveness of ultra-hypofractionated radiotherapy and conventionally fractionated radiotherapy for intermediate-to-high-risk localized prostate cancer from the Chinese payer perspective. Methods: We developed a Markov model with a 15-year time horizon to compare the cost and effectiveness of ultra-hypofractionated radiotherapy with those of conventionally fractionated radiotherapy for localized intermediate-to-high-risk prostate cancer. Outcomes were measured in quality-adjusted life-years (QALYs), incremental cost-effectiveness ratio (ICER), and willingness-to-pay (WTP). Univariable and probability sensitivity analyses were performed to evaluate the robustness of the Markov model. Results: Based on the Markov model, the conventionally fractionated radiotherapy yielded 2.32 QALYs compared with 2.14 QALYs in the ultra-hypofractionated radiotherapy in China. The cost of ultra-hypofractionated radiotherapy was found to be decreased by about 14% folds ($4251.04) in comparison to that of conventionally fractionated radiotherapy. The ICER of conventionally fractionated radiotherapy versus the ultra-hypofractionated radiotherapy was $23,616.89 per QALY in China. The failure-free survival (FFS) with grade two or worse urinary toxicity and the discount rate per annum were the most sensitive parameters utilized in the ultra-hypofractionated radiotherapy. The cost effectiveness acceptability curve showed that conventionally fractionated radiotherapy had a 57.7% probability of being cost-effective under the Chinese WTP threshold. Conclusion: From the perspective of the Chinese payers, the ultra-hypofractionated radiotherapy was not a cost-effective strategy compared with the conventionally fractionated radiotherapy for patients with localized intermediate-to-high-risk prostate cancer from the perspective of the Chinese payers.Nevertheless, reduction of the grade two or worse urinary toxicity of the ultra-hypofractionated radiotherapy could alter the results. Keywords: cost-effectiveness analysis, ultra-hypofractionated radiotherapy, conventionally fractionated radiotherapy, prostate cancer, Markov model.